2020
DOI: 10.3389/fnins.2020.00700
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI Signal Complexity Analysis Using Sample Entropy

Abstract: Resting-state functional magnetic resonance imaging (rs-fMRI) is an immensely powerful method in neuroscience that uses the blood oxygenation level-dependent (BOLD) signal to record and analyze neural activity in the brain. We examined the complexity of brain activity acquired by rs-fMRI to determine whether it exhibits variation across brain regions. In this study the complexity of regional brain activity was analyzed by calculating the sample entropy of 200 whole-brain BOLD volumes as well as of distinct bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 33 publications
9
36
2
Order By: Relevance
“…This study reinforces the existence of complex dynamics in brain function [29] and provides further evidence for the hypothesis of distinct complexity features in human behaviour and cognition [31]. Our results suggest that: (i ) task-based and rsfMRI signals exhibit temporal complexity, inferred by Hurst exponent and multiscale entropy, (ii ) rest and task periods of brain function can be distinguished from each other with high accuracy based on their temporal complexity profiles, (iii ) cognitive load can suppress the complex dynamics of fMRI in contrast to the resting state, (iv ) spatial distribution of Hurst exponent and entropy-based complexity index in fMRI are highly correlated, and (v ) the frontoparietal network and default mode network represent maximal complex behaviour compared to the rest of the brain regardless of the mental state.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This study reinforces the existence of complex dynamics in brain function [29] and provides further evidence for the hypothesis of distinct complexity features in human behaviour and cognition [31]. Our results suggest that: (i ) task-based and rsfMRI signals exhibit temporal complexity, inferred by Hurst exponent and multiscale entropy, (ii ) rest and task periods of brain function can be distinguished from each other with high accuracy based on their temporal complexity profiles, (iii ) cognitive load can suppress the complex dynamics of fMRI in contrast to the resting state, (iv ) spatial distribution of Hurst exponent and entropy-based complexity index in fMRI are highly correlated, and (v ) the frontoparietal network and default mode network represent maximal complex behaviour compared to the rest of the brain regardless of the mental state.…”
Section: Discussionsupporting
confidence: 87%
“…Region-specific properties of fMRI were also studied in [32] where higher complexity was reported in sub-cortical regions such as the caudate, the olfactory gyrus, the amygdala, and the hippocampus, whilst primary sensorimotor and visual areas were associated with lower complexity. Nezafati et al [29] confirmed this finding and also, showed that networks exhibit distinct complex properties which may change between resting state and during task performance. Omidvarnia et al [1] reproduced the findings of RSN-specific temporal complexity in rsfMRI and lower complexity of sub-cortical regions in contrast to cortical networks across 1000 healthy subjects.…”
Section: Temporal Complexity and Brain Dynamicsmentioning
confidence: 68%
See 2 more Smart Citations
“…Time-varying analysis (rather than measures averaged over the whole scan, like typical correlation-based functional connectivity) attempts to characterize the underlying low-dimensional structure of the brain’s dynamics ( Hutchison et al, 2013 ; Keilholz et al, 2017 ; Preti et al, 2017 ). At the voxel/parcel level, concepts from non-linear dynamics like entropy, Hurst exponent and Lyapunov exponent have been used to characterize the complexity of the signal from each area, based on the hypothesis that the complexity of the BOLD signal carries information about the complexity of the underlying neural activity ( Wang et al, 2011 ; Yang et al, 2013 ; Ciuciu et al, 2014 ; Jia et al, 2017 ; Wang Y. et al, 2018 ; Liu et al, 2018 , 2019 ; Song et al, 2019 ; Nezafati et al, 2020 ). However, these metrics are difficult to interpret in the context of rs-fMRI.…”
Section: Introductionmentioning
confidence: 99%